Squash, Spaghetti—Cucurbita pepo L. - James M. Stephens (EDIS, 2003)
This document provides an overview of spaghetti squash (Cucurbita pepo L.), highlighting its unique stringy flesh that resembles spaghetti when cooked. It describes the fruit’s physical characteristics, culinary uses, and cultivation practices suitable for Florida’s climate. The plant requires warm weather, proper spacing, and pollination by bees, with harvest occurring 70–80 days after seeding. Common pests include mildews and pickleworms. Proper storage can extend shelf life for several weeks. Original publication date May 1994.